PEMBELAJARAN MATEMATIKA HUMANIS DENGAN METAPHORICAL THINKING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA - Heris Hendriana (IKIP Siliwangi and I-MES, 2012)
This research uses experimental method pretest posttest disign. The purpose of this study was to determine the increase in the confidence of students in mathematics in mathematics learning with metaphorical thinking humanist. This research was conducted at the Junior High School level. The instrument used in this study is the achievement test and questionnaire about students' confidence. The results showed that mathematics humanists with metaphorical thinking (MT) is superior to conventional learning in enhancing the confidence of students, viewed as a whole and based on the level of the school and the beginning of students' mathematical abilities. There is a high association between KAM and confidence in the classroom with learning metaphorical thinking, and the conventional class association between KAM and confidence quite enough. The confidence of students whose learning approach metaphorical thinking (MT) is better than using the normal way (CB), students gain confidence to approach learning MT and CB are in qualifying was.